Exploring Gender Differences in Mental Health: Attitudes towards Help-Seeking and Service Utilization - Tanya Kaushik; Smriti Sethi (International Journal of Behavioral Sciences, 2024)
Mental health is a complex topic that requires understanding of gender disparities in the use of mental health services and the behavior of seeking assistance. Development of legislation and initiatives aiming at raising awareness and availability of mental health care depends on this knowledge. Maintaining healthy relationships, limiting disease development, managing symptoms, increasing production, and fighting cultural prejudice all depend on mental health therapies. Gender expectations, socialising, stigma, and the belief that women are inferior are among the elements influencing these variances. Development of mental health treatments, policies, and initiatives responsive to gender variations was guided by a secondary research assessment of fifty studies on gender discrepancies in attitudes towards getting assistance for mental health disorders. A literature review from 50 established studies ranging from 2014-2024 was done with the help of PubMed, Google Scholar, Science Direct, Frontiers. While males showed obvious trends, women in western nations used more healthcare facilities and showed higher understanding of mental health. Because of low reading skills, poor education, and gender-based discrimination, women in India were stigmatised and so deprived of access to sufficient healthcare services. Particularly for women, mobile clinics can provide mental health treatments and education in far-off areas, therefore optimising access to medical facilities. Enhancing financial support for mental health research and promoting policy reforms can help close the gender gap, ensuring fairer access to mental health services worldwide.
Keywords: Mental health; gender differences; healthcare access; help-seeking attitude; service utilization patterns